2018
DOI: 10.1111/jcmm.13524
|View full text |Cite
|
Sign up to set email alerts
|

Propofol exposure during early gestation impairs learning and memory in rat offspring by inhibiting the acetylation of histone

Abstract: Propofol is widely used in clinical practice, including non‐obstetric surgery in pregnant women. Previously, we found that propofol anaesthesia in maternal rats during the third trimester (E18) caused learning and memory impairment to the offspring rats, but how about the exposure during early pregnancy and the underlying mechanisms? Histone acetylation plays an important role in synaptic plasticity. In this study, propofol was administered to the pregnant rats in the early pregnancy (E7). The learning and mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…However, emergency surgeries such as trauma surgery, emergency cesarean delivery and fetal intrauterine surgery make general anesthesia inevitable during pregnancy. Because most general anesthetics with strong lipid-solubility can pass across the placental barrier, maternal anesthesia can generate negative effects on the fetal nervous system, (Wang Y. et al, 2012; Zheng et al, 2013; Lin et al, 2018). The Food and Drug Agency (FDA) issued an official warning that children under 3 years of age or pregnant women in the third trimester who would undergo anesthesia for more than 3 h or more anesthesia procedures might exert adverse consequences of children’s brain development (Andropoulos and Greene, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, emergency surgeries such as trauma surgery, emergency cesarean delivery and fetal intrauterine surgery make general anesthesia inevitable during pregnancy. Because most general anesthetics with strong lipid-solubility can pass across the placental barrier, maternal anesthesia can generate negative effects on the fetal nervous system, (Wang Y. et al, 2012; Zheng et al, 2013; Lin et al, 2018). The Food and Drug Agency (FDA) issued an official warning that children under 3 years of age or pregnant women in the third trimester who would undergo anesthesia for more than 3 h or more anesthesia procedures might exert adverse consequences of children’s brain development (Andropoulos and Greene, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The data upon were all tested on the postnatal 33 days, 1 h after the fear conditioning test. When explored the GA effects on the maternal-offspring module, the researchers indicated that infusion with propofol in maternal rats on gestational day-7 leads to impairment of learning and memory in off-spring, increased the protein levels of HDAC2, decreased the levels of acetylated H3K14 and H4K12 ( Lin et al, 2018b ). The different results of the different anesthetics suggest that the histone acetylation may have the drug specificity.…”
Section: Post-translational Modifications Of Histonesmentioning
confidence: 99%
“…It is well known that epigenetic alterations or genetic modulation of epigenetic regulators plays important roles in carcinogenesis . Many studies show that the anticancer effect of propofol is potentially due to regulation of the epigenetic pathway in cancer …”
Section: Epigenetic Pathwaysmentioning
confidence: 99%
“…Liu et al. proved that propofol could affect the offspring's learning and memory by inhibiting histone acetylation . In 2017, Liu et al.…”
Section: Epigenetic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation